Lessons from the PROTECT-CH COVID-19 platform trial in care homes - Philip M Bath; Jonathan Ball; Matthew Boyd; Heather Gage; Matthew Glover; Maureen Godfrey; Bruce Guthrie; Jonathan Hewitt; Robert Howard; Thomas Jaki; Edmund Juszczak; Daniel Lasserson; et al. (Health Technology Assessment)
Background Coronavirus disease-2019 was associated with significant mortality and morbidity in care homes in 2020–1. Repurposed antiviral drugs might reduce morbidity and mortality through reducing viral transmission, infection, replication and inflammation. We aimed to compare the safety and efficacy of potential antiviral drugs in care home residents. Methods We designed a cluster-randomised, open-label, blinded end-point platform trial to test drugs in a postexposure prophylaxis paradigm. Participants aged 65+ years from United Kingdom care homes, with or without nursing, were eligible for participation. Care homes were to be allocated at random by computer to administer 42 days of antiviral agent (ciclesonide or niclosamide) plus standard care versus standard care alone to residents. The primary outcome at 60 days after randomisation comprised the most serious outcome, which was defined as all-cause mortality, all-cause hospitalisation, severe acute respiratory syndrome coronavirus 2 infection or no infection. Analysis would be by intention to treat using ordinal logistic regression. Other outcomes included individual components of the primary outcome, transmission, plus health economic and process evaluation outcomes. The planned sample size was 300 care homes corresponding to 9600 residents. With ~40% of care homes predicted to develop an outbreak during the trial, we needed to recruit 750 homes/24,000 residents. Results We initiated the trial including protocol, approvals, insurance, website, database, data algorithms, intervention selection and training materials. We built a network of principal investigators and staff (91) and care homes (299) to support the trial. However, we never contracted care homes or general practitioners since the trial was stopped in September 2021, as vaccination in care homes had significantly reduced infections. Multiple delays significantly delayed the start date, such as: (1) reduced prioritisation of pandemic trials in 2021; (2) cumbersome mechanisms for choosing the investigational medicinal products; (3) contracting between National Institute for Health and Care Research and the investigational medicinal product manufacturers; (4) publicising the investigational medicinal products; (5) identification of sufficient numbers of care homes; (6) identification and contracting with several thousand general practitioners; (7) limited research nurse availability and (8) identification of adequate insurance to cover care homes for research. Generic challenges included working across the four home nations with their different structures and regulations. Limitations The feasibility of contracting between the sponsor and the principal investigators, general practitioners and care homes; screening, consent and treatment of care home residents; data acquisition and the potential benefit of postexposure prophylaxis were never tested. Conclusions The success of vaccination meant that the role of postexposure prophylaxis of coronavirus disease-2019 in care home residents was not tested. Significant progress was made in developing the infrastructure and expertise necessary for a large-scale clinical trial of investigational medicinal products in United Kingdom care homes. Future work The role of postexposure prophylaxis of coronavirus disease-2019 in care home residents remains undefined. Significant logistical barriers to conducting research in care homes need to be removed urgently before future studies are possible. Further work is required to develop the infrastructure for clinical trials of investigational medicinal products in care homes. Serious consideration should be given to building and then hibernating a pandemic-ready platform trial suitable for care home research. Funding This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR133443. Plain language summary Coronavirus disease-2019 (COVID-19) was associated with significant harm and death in care homes in 2020–1. Existing drugs that were used for other purposes might have reduced the infection and poor outcome. We designed a trial to test whether drugs given to most residents in a care home once someone had COVID-19 might reduce the infection and poor outcomes. Residents would be those in a United Kingdom care home for older people. Care homes (not residents) were to be chosen at random (like a toss of a coin) to give one of two drugs, or no drugs, for 42 days to consenting residents. All participants would receive the best medical care. After 60 days, we were to assess whether residents had died, been admitted to hospital, had developed COVID-19 in their care home or had no infection. We also planned to measure whether the treatments were cost-effective and how the all the trial procedures worked. We were planning to recruit 750 homes and 24,000 residents. We designed the trial and all its computer and training systems and built a network of doctors, nurses and care homes to support the trial. However, the success of vaccination against COVID-19, especially in care home residents, meant we never contracted any of these, and we stopped the trial in September 2021. We faced multiple delays, including how to choose the drugs and contract with the drug manufacturers, find sufficient numbers of care homes, general practitioners and nurses who were interested in joining, how to provide insurance cover for the care homes and how to work across the various legal systems in England, Northern Ireland, Scotland and Wales. The success of vaccination meant that we could never test whether drugs might reduce COVID-19 and its effects in care homes. We strongly suggest that it would be worth building a similar trial and then ‘parking’ it in case there is another pandemic that threatens care home residents and effective vaccination is not yet available.